Use of unified theory of acceptance and use of technology model for telemedicine services: an exploratory study - Irfanahemad, A. S.; Nandakumar, B. S.; K., Radhika (International Journal Of Community Medicine And Public Health, 2018)
Background: While quality health-care is considered a fundamental human right for all citizens; the challenge remains in making it accessible to all. Information systems have been identified as possible solution that can be used to alleviate disparity between rural and urban healthcare services and bridge the digital divide. Literature has suggested that one of the barriers for successful implementation of health information system is the user acceptance by health care personnel. The main objective of this study is to assess perceived usefulness, relative advantages of telemedicine technology among health personnel of selected district. Methods: This is a cross-sectional study, using Semi-structured questionnaire. Data was collected from research participants from PHCs of Bijapur district, during July to November 2017. Results: In general the health-care personnel were aware of the benefit of tele-medicine to improve effectiveness and efficiency of the health care system. The barriers to the effective implementation of tele-medicine include lack of knowledge and lack of awareness regarding use and usage of the tele-medicine system. Conclusions: Health care personnel do acknowledge that tele-medicine can help to increase the effectiveness of the healthcare system. In general the acceptance of tele-medicine among healthcare personnel is positive. However in order to integrate it into standard work practices, specific training and capacity building for tele services is essential among health care personnel.